Conductive paste composition for external electrode, external electrode obtained by firing the same, and multilayer ceramic capacitor
Patent Information
- Application Number
- KR1020240161446
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2044-11-13
Smart Images

Figure 112024125075921-PAT00003_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a conductive paste composition for forming external electrodes and a multilayer ceramic capacitor comprising the same. Background Technology
[0002] Multilayer ceramic capacitors (MLCCs) can be used in various electronic devices as they are small and guarantee high capacitance. As shown in FIG. 1, the multilayer ceramic capacitor is formed by alternately stacking dielectric layers (10) and internal electrodes (20) and firing a paste containing a conductive material onto a ceramic body to form an external electrode (30) that is electrically connected to the internal electrode, and forming a plating layer (40) on the outside of the external electrode (30).
[0003] A paste composition for external electrodes may include a conductive material and a glass frit. When forming external electrodes for MLCCs, defects such as blistering, glass surface precipitation, reduced sintering density, reduced adhesive strength, poor contact with internal electrodes, cracking, and plating solution penetration may occur depending on the combination of sintering process conditions and the characteristics of the metal powder and glass frit; therefore, selecting a glass frit suitable for specific MLCC process conditions is very important.
[0004] In particular, for MLCCs used for high frequency, high voltage, and AC voltage, ESR (equivalent series resistance) and heat generation characteristics are very important, and to improve these characteristics, it is important to maximize the contact cross-sectional area between the internal electrode and the external electrode. In the cross-sectional photograph of a general MLCC shown in FIG. 2, even if the contact between the internal electrode (20) and the external electrode (30) appears partially broken, as long as they are connected by a certain portion of the reaction layer (25), characteristics such as capacitance or dielectric loss are not degraded. However, in C0G series MLCCs, the dielectric ceramic used is often difficult to sinter compared to X5R and X7R series dielectric ceramics, so the ceramic shrinkage rate is low during sintering. Consequently, after sintering, the internal electrode may not be exposed to the surface of both ends of the MLCC and may sink into the ceramic interface. In such cases, if the contact between the internal and external electrodes deteriorates, defects such as capacitance dispersion and increased dielectric loss may occur. In addition, even if capacitance variation does not occur in high-voltage MLCCs, it is necessary to maximize contact between the internal and external electrodes to improve heat generation characteristics. For the above reasons, it is necessary to optimize the paste composition for the external electrode that can increase contact between the internal and external electrodes. The problem to be solved
[0005] The present invention aims to solve such conventional problems by providing a conductive paste composition for an external electrode that improves contact between the internal and external electrodes in a multilayer ceramic capacitor without causing various problems such as cracking, strength reduction, and blistering. However, this objective is exemplary and does not limit the scope of the present invention. means of solving the problem
[0006] According to one aspect of the present invention, a conductive paste composition for an external electrode is provided.
[0007] The above conductive paste composition for external electrodes comprises: conductive metal powder; and aBaO-bCaO-cZnO-dB2O3-eSiO2-fAl2O3-gTM x O y Comprising a glass frit composed of the chemical formula -hA2O; wherein TM is a transition metal selected from the group consisting of vanadium (V) and manganese (Mn), A is an alkali metal selected from the group consisting of lithium (Li), sodium (Na), and potassium (K), x,y > o, a+b+c+d+e+f+g+h = 100 wt%, and 0 <a+b<45, 30<c<40, 15≤d≤25, 0<e<10, 0<f<10, 5<g<10, h≤2, 40≤a+b+d≤61이고, 상기 글라스 프릿의 유리전이온도(Tg)는 550℃ 이하이고, 소성 후 잔탄량이 1,000ppm 미만인 것을 특징으로 할 수 있다.
[0008] According to one embodiment, the content of the glass frit may be 5 to 20 parts by weight per 100 parts by weight of the composition.
[0009] According to one embodiment, the conductive metal powder may be characterized as being copper (Cu) powder.
[0010] According to one embodiment, the copper (Cu) powder may be characterized by having an average particle size of 0.1 to 5 μm.
[0011] According to one embodiment, the average particle size of the glass frit may be 3 μm or less.
[0012] According to one embodiment, the conductive paste composition for the external electrode may be characterized by having a viscosity of 20 to 60 Pa·S.
[0013] According to another aspect of the present invention, an external electrode is provided by firing the conductive paste composition for the external electrode.
[0014] According to another aspect of the present invention, a multilayer ceramic capacitor having the external electrode is provided.
[0015] According to one embodiment, the multilayer ceramic capacitor may be characterized in that dielectric layers and internal electrodes are alternately stacked, and the external electrode is electrically connected to the internal electrode by a reaction layer formed at least one interface between the internal electrode and the external electrode. Effects of the invention
[0016] According to an embodiment of the present invention as described above, a reaction layer is formed at the interface between the external electrode and the internal electrode, thereby increasing adhesive strength without crack formation and increasing contact between the internal electrode and the external electrode. In addition, a multilayer ceramic capacitor with improved ESR characteristics can be effectively realized.
[0017] Of course, the scope of the present invention is not limited by these effects. Brief explanation of the drawing
[0018] Figure 1 is a schematic cross-sectional view of a typical MLCC. Figure 2 is a cross-sectional photograph of a typical MLCC. FIG. 3 is a cross-sectional view of a multilayer ceramic capacitor manufactured by firing a conductive paste composition for external electrodes according to an embodiment of the present invention. FIGS. 4 and 5 are cross-sectional views of a multilayer ceramic capacitor manufactured by firing a conductive paste composition for an external electrode according to a comparative example of the present invention. Specific details for implementing the invention
[0019] Hereinafter, various embodiments of the present invention will be described in detail with reference to the attached drawings. The embodiments of the present invention are provided to more fully explain the present invention to those skilled in the art, and the following embodiments may be modified in various different forms, and the scope of the present invention is not limited to the following embodiments. Rather, these embodiments are provided to make the present disclosure more faithful and complete and to fully convey the spirit of the present invention to those skilled in the art. In addition, the thickness or size of each layer in the drawings is exaggerated for convenience and clarity of explanation.
[0020] A conductive paste composition for an external electrode according to one embodiment of the present invention comprises a conductive metal powder and aBaO-bCaO-cZnO-dB2O3-eSiO2-fAl2O3-gTM x O y It is characterized by comprising a glass frit composed of the chemical formula -hA2O. The composition may further include a binder, a dispersant, a solvent, and other additives as needed.
[0021] The components included in the conductive paste composition for external electrodes according to a specific embodiment of the present invention will be described in more detail below.
[0022] (A) Conductive metal powder
[0023] As conductive metal powder for forming external electrodes, metals such as Ag, Cu, Ni, and Pd can be used, and preferably, copper (Cu) is used. Copper powder can be used alone or in combination with various shapes and particle sizes, taking into account the firing temperature, debinding characteristics, and sintering density of the external electrode. The average particle size of the copper powder is not particularly limited, but is preferably 0.1 to 5 μm.
[0024] (B) glass frit
[0025] The glass frit used in the present invention functions to maintain adhesive strength by bonding the external electrode with the ceramic body and to improve the sintering density of the external electrode by inducing liquid phase sintering.
[0026] Generally, the external electrodes of an MLCC are formed by applying a paste of conductive metal powder and then sintering it at a temperature of approximately 700°C to 950°C. At this time, the glass frit must soften after the temperature at which the organic binder in the paste is removed—for example, before the copper powder undergoes solid-state sintering—so that it can come into contact with and wet the copper powder. To achieve this, it is necessary to appropriately control the glass transition temperature (Tg) or softening point of the glass frit. Since the bonding strength with the copper powder decreases if the glass frit softens too early, and conversely, sintering with the copper powder may become difficult if it softens too late, it is important to optimize the glass transition temperature and softening point of the glass frit in the paste to match the temperature profile of the sintering process.
[0027] To this end, the glass frit according to an embodiment of the present invention is aBaO-bCaO-cZnO-dB2O3-eSiO2-fAl2O3-gTM x O y Composed of the chemical formula -hA2O, where TM is a transition metal selected from the group consisting of vanadium (V) and manganese (Mn), A is an alkali metal selected from the group consisting of lithium (Li), sodium (Na), and potassium (K), x,y > o, a+b+c+d+e+f+g+h = 100 wt%, and 0 <a+b<45, 30<c<40, 15≤d≤25, 0<e<10, 0<f<10, 5<g<10, h≤2, 40≤a+b+d≤61 의 조성비를 갖는다.
[0028] Specifically, barium oxide (BaO) and calcium oxide (CaO) included in the composition of the glass frit are alkaline earth metal oxides that serve to control the glass transition temperature or softening point of the glass frit. When these are appropriately included, the glass frit can be sufficiently softened within the sintering temperature range of the paste, thereby increasing adhesion. It is preferable to use a mixture of BaO and CaO, with a total content of greater than 0 and less than 45 weight percent.
[0029] Similarly, boron oxide (B2O3) is a substance that helps lower the glass transition temperature and softening point of the glass frit, thereby improving wettability with conductive metal powder during the sintering process and ensuring desired bonding characteristics. In addition, B2O3 acts as a glass former, contributing to stabilizing the structure of the glass frit and increasing its mechanical strength. In the present invention, it is preferable to add 15 to 25 weight percent of B2O3. If less than 15 weight percent is added, the effect of improving wettability with metal powder and mechanical strength is insufficient, and if more than 25 weight percent is added, softening occurs at a temperature lower than the sintering temperature, resulting in a decrease in the bonding characteristics of the external electrode and a decrease in thermal and chemical stability.
[0030] In addition, as a preferred embodiment of the present invention, it is preferable that the sum of the components of BaO, CaO, and B2O3 is 40 to 61 weight%. By applying a content of BaO+CaO+B2O3 in the glass frit of 40 to 61 weight%, the glass transition temperature (Tg) of the glass frit can be controlled to be 550°C or lower. If the glass transition temperature of the glass frit is higher than 550°C, liquid-phase sintering cannot be induced during the firing process of the external electrode, and sintering between metal particles begins first, resulting in a problem where the density of the final external electrode is reduced. Therefore, it is important to control the glass transition temperature (Tg) of the glass frit to 550°C or lower. If the content of BaO+CaO+B2O3 in the glass frit is less than 40 weight%, the glass transition temperature (Tg) of the glass frit cannot be lowered to 550℃ or lower, and if it exceeds 61 weight%, it may lead to a decrease in chemical durability and mechanical strength.
[0031] Meanwhile, the zinc oxide (ZnO) used in the composition of the glass frit above can chemically react with the internal electrode during the sintering process to form a thin reaction layer at the interface. This reaction layer can strengthen the contact between the internal electrode and the external electrode, thereby enhancing electrical and mechanical connectivity.
[0032] When the ZnO content is 30 wt% or less, it is difficult to effectively form a reaction layer, making it difficult to achieve the desired effects in adhesive strength and internal-external electrode contact. Therefore, it is desirable to add more than 30 wt% of ZnO. However, if the ZnO content is excessively high at 40 wt% or more, the reaction layer formed at the interface between the internal and external electrodes becomes excessively thick. This may lead to a decrease in electrical contact characteristics or an increase in interfacial resistance, and there is also a risk of reduced bonding strength. Therefore, it is desirable to add less than 40 wt% of ZnO.
[0033] Meanwhile, silicon dioxide (SiO2), like B2O3, acts as a glass former to stabilize the structure of the glass frit and improve acid resistance. However, if the SiO2 content is 10 weight% or more, the glass transition temperature of the glass frit increases and the wettability to metal powder decreases, which may cause defects such as segregation on the surface of the external electrode after firing. Therefore, in the present invention, it is preferable that the SiO2 content be less than 10 weight%.
[0034] In addition, it is preferable that the content of aluminum oxide (Al2O3) be less than 10 weight%. Although Al2O3 improves the mechanical strength and heat resistance of the glass frit, if the content is excessive, the glass-forming characteristics of the glass frit may weaken or the softening point may increase, making sintering difficult; therefore, it is preferable to add it in an amount of 10 weight% or less.
[0035] In the above glass frit composition, one or more transition metal oxides (TM) selected from the group consisting of vanadium (V) oxide and manganese (Mn) oxide x O y It includes ). For example, oxides of the form such as V2O5 and MnO2 may be used. The transition metal oxide component may be included in an amount greater than 5 wt% and less than 10 wt%. If the content of the transition metal oxide is 5 wt% or less, the wettability of the glass frit to the metal powder is reduced, which may cause problems such as glass segregation or a decrease in density after firing. On the other hand, if it is included in an excessive amount of 10 wt% or more, devitrification may occur due to a decrease in the stability of the glass phase.
[0036] Based on the total composition of the glass frit, an alkali metal compound may be included in an amount of 2 weight% or less. If the content of the alkali metal compound increases to more than 2 weight%, reactivity with the ceramic body increases, but it may cause cracking, thereby reducing adhesive strength and potentially lowering the reliability of the MLCC. The alkali metal used here is Li, Na, K, etc., and the type is not limited in the present invention. Furthermore, the form of the alkali metal used in the manufacture of the glass frit may be in the form of its hydroxides, carbonates, chlorides, etc., and is also not limited.
[0037] The glass frit having the composition of the present invention described above is not limited to its manufacturing method or the form of its raw materials. For example, it may be manufactured by melting oxides at a high temperature, rapidly cooling them, and then grinding them, but is not limited thereto. The average particle size of the glass frit is not particularly limited, but considering the thickness of the external electrode, it is preferable that it be 3.0 μm or less, and more preferably 1.3 μm or less.
[0038] The content of the glass frit of the present invention may be included in an amount of 5 to 20 parts by weight per 100 parts by weight of the conductive paste composition.
[0039] Since MLCC external electrodes are mainly formed by a dip coating process using paste, it is desirable to produce paste with a high viscosity of about 20 to 60 Pa·s to be suitable for this process, and to ensure dispersibility at high viscosity, the paste is produced using a 3-roll mill or a high-pressure homogeneizer.
[0040] The conductive paste composition for external electrodes of the present invention, having the composition as described above, is characterized in that residual carbon may be incorporated during firing, but the amount of residual carbon after firing is less than 1,000 ppm. If the residual carbon content of the glass frit is 1,000 ppm or more, it may cause blistering defects during the firing of MLCC external electrodes, and there is a problem in that the density of the external electrode is lowered by reducing the fluidity and wettability of the glass or hindering the sinterability of the metal powder.
[0041] A multilayer ceramic capacitor (MLCC) according to another embodiment of the present invention has a structure in which dielectric layers and internal electrodes are alternately stacked. The dielectric layer is a ceramic formed by sintering a dielectric paste. The internal electrodes are not particularly limited, but Ni, Cu, or an alloy thereof are preferred.
[0042] The external electrode according to an embodiment of the present invention is formed by firing a conductive paste composition for an external electrode made of the composition described above. At this time, the firing temperature may be performed at approximately 700 to 950°C. The external electrode formed at both ends of the MLCC comes into contact with the internal electrode and, when an external power source is applied, serves to impart opposite polarities to a plurality of internal electrode layers. It is firmly attached to the dielectric body and serves to prevent internal penetration of foreign substances and moisture during a subsequent plating process.
[0043] Specifically, the external electrode can be electrically connected to the internal electrode by a reaction layer formed at least at one interface with the internal electrode. In this case, it is preferable that the reaction layer be formed with a thickness that has high adhesive strength but does not cause cracking.
[0044] The present invention will be explained in more detail below through the following examples, but the scope of the present invention is not limited to these examples.
[0045] <Example>
[0046] Glass frit satisfying the composition of Table 1 was prepared and weighed together with copper powder so that the ratio of copper to glass frit was 90 / 10. This was pre-dispersed and mixed with an acrylic binder and a dispersant in a terpineol (α-terpineol) solvent, and then finally dispersed using a high-pressure disperser to produce a copper paste for MLCC external electrodes with a viscosity of 40 Pa·s.
[0047] The copper paste described above was applied to both ends of an MLCC having a size of 3.2*1.6*1.6 mm using a dip coating method, dried at 120°C for 30 minutes, and then fired at a maximum temperature of 810°C to form an external electrode layer. The MLCC with the formed external electrode was polished by vibration polishing to polish the surface of the external electrode, and then nickel and tin plating layers were applied to complete the MLCC.
[0048] The physical properties of the glass frit were evaluated as follows.
[0049] 1) Remaining carbon content (ppm): Measured using a carbon-sulfur analyzer (CS analyzer) that measures the amount of CO / CO2 gas generated by heat-treating the sample at a high temperature in an oxidizing atmosphere.
[0050] 2) Glass transition temperature (Tg): Measured by heating at a heating rate of 10℃ / min using differential thermal analysis (DTA).
[0051] 3) Average particle size: The particle size was measured by averaging the values from images obtained using a scanning electron microscope (SEM).
[0052] division Glass frit composition (wt%) Glass frit properties A2O BaO CaO ZnO B2O3 SiO2 Al2O3 Tm x O y BaO + CaO BaO + CaO + B2O3 Remaining carbon content (ppm) Tg(℃) Average particle size (㎛) Example 1 0.5 34 5 31 15 3.5 5.5 5.5 39 54 450 520 2.0 Example 2 0 29 4 32 20.5 4.5 4.5 5.5 33 53.5 345 540 1.3 Comparative Example 1 17.5 18 2.5 32 20 3.5 1 5.5 20.5 40.5 600 540 3.0 Comparative Example 2 0 17.5 2.5 32 20 21.5 1 5.5 20 40 600 560 3.0 Comparative Example 3 0 33 5 32 20 4.5 1 4.5 38 58 600 520 2.0 Comparative Example 4 2 14 5 38 20 4.5 7.5 9 19 39 600 560 2.0 Comparative Example 5 0 39 5 22 17 3 5 9 44 61 980 512 3.0 Comparative Example 6 0 43.5 4 19 16.5 4.5 12.5 0 47.5 64 1800 555 3.0 Comparative Example 7 4 4 4 36 17 25 2.5 7.5 3 25 660 55 2.0
[0053] (A2O: Alkali metal oxide)
[0054] After firing, optical microscope and SEM analysis of the surface and cross-section of each sample were performed to check for blister defects, glass surface precipitation defects, density of the external electrode layer, formation of a reaction layer between the MLCC body and the external electrode layer, and internal-external electrode contact.
[0055] Acid resistance was verified through cross-sectional analysis of each sample based on whether the plating solution had diffused into the external electrode layer. In addition, 100 of each sample were fabricated and subjected to non-destructive ultrasonic testing to determine the frequency of crack formation. ESR was measured using an impedance analyzer at frequencies ranging from 10 MHz to 1000 MHz.
[0056] The results of the physical property measurements of each sample were evaluated relatively and are shown in Table 2.
[0057] division Blister (glass precipitation) Whether cracks have formed Adhesion strength Plasticity density Whether a reaction layer is formed Acid resistance of plating solution Internal-external electrode contact ESR Example 1 ◎ ◎ ◎ ○ ◎ ○ ◎ ◎ Example 2 ○ ◎ ○ ○ ◎ ◎ ◎ ◎ Comparative Example 1 X X △ X ◎ ◎ X X Comparative Example 2 ○ X △ X ◎ ◎ X X Comparative Example 3 ○ X △ X ◎ ◎ X X Comparative Example 4 ○ X △ X ◎ ◎ X X Comparative Example 5 △ ○ ○ ○ X △ △ △ Comparative Example 6 X ○ △ X X ◎ △ △ Comparative Example 7 X △ △ ◎ ◎ ○ △ △
[0058] (◎: Very Good, ○: Good, △: Average, X: Bad)
[0059] Example 1
[0060] A glass frit with a composition of 0.5Na2O-34BaO-5CaO-31ZnO-15B2O3-3.5SiO2-5.5Al2O3-5.5MnO2 was prepared to have an average particle size of 2.0㎛. As shown in Table 1, this glass frit had a glass transition temperature of 520℃ and a residual carbon content of 450ppm.
[0061] As shown in Table 2, the physical properties of the MLCCs made with the composition according to Example 1 were all good.
[0062] In the cross-sectional photograph of the MLCC according to Example 1 shown in Fig. 3, it was confirmed that a reaction layer (25) was well formed at the interface between the internal electrode (20) and the external electrode (30).
[0063] As a result of checking whether the plating solution had diffused into the external electrode layer, no traces of plating solution penetration were found in any of them. In addition, it was confirmed that the frequency of crack formation was 0 / 100, and excellent adhesion strength was observed in the terminal adhesion strength evaluation, and the ESR characteristics were also excellent.
[0064] Example 2
[0065] A glass frit with a composition of 29BaO-4CaO-32ZnO-20.5B2O3-4.5SiO2-4.5Al2O3-5.5V2O5 was prepared to have an average particle size of 1.3㎛. This glass frit had a glass transition temperature of 540℃ and a residual carbon content of 345ppm.
[0066] As shown in Table 2, the physical properties of the MLCCs fabricated with the composition according to Example 2 were all good. When checking whether the plating solution had diffused into the external electrode layer, no traces of plating solution penetration were found in any of them. In addition, it was confirmed that the frequency of crack formation was 0 / 100, and excellent adhesion strength was observed in the terminal adhesion strength evaluation, and the ESR characteristics were also excellent.
[0067] Comparative Example 1
[0068] A glass frit with a composition of 12.5Li2O-5K2O-18BaO-2.5CaO-32ZnO-20B2O3-3.5SiO2-1Al2O3-5.5V2O5 was prepared to have an average particle size of 3.0㎛. This glass frit had a glass transition temperature of 540℃ and a residual carbon content of 600ppm.
[0069] A photograph of an MLCC made with the composition according to Comparative Example 1 is shown in Fig. 4. Referring to Fig. 4, it was confirmed that a reaction layer was formed, but the glass surface elution was severe, and cracks occurred at a frequency of 22ea / 1000ea, resulting in a decrease in adhesion strength and consequently, a decrease in ESR characteristics. This is confirmed to be because the excessive content of alkali metal oxides Li2O and K2O in the glass frit increases reactivity with the ceramic body, but causes cracks, thereby actually lowering the adhesion strength.
[0070] Comparative Example 2
[0071] A glass frit with a composition of 17.5BaO-2.5CaO-32ZnO-20B2O3-21.5SiO2-1Al2O3-5.5V2O5 was prepared to have an average particle size of 3.0㎛. This glass frit had a glass transition temperature of 560℃ and a residual carbon content of 600ppm.
[0072] As a result of measuring the physical properties of an MLCC made with the composition according to Comparative Example 2, it was confirmed that the glass transition temperature of the glass frit increased and the sintering density was low due to the excessive SiO2 content in the glass frit.
[0073] Comparative Example 3
[0074] A glass frit with a composition of 33BaO-5CaO-32ZnO-20B2O3-4.5SiO2-1Al2O3-4.5V2O5 was prepared to have an average particle size of 2.0㎛. This glass frit had a glass transition temperature of 520℃ and a residual carbon content of 600ppm.
[0075] As a result of measuring the physical properties of an MLCC made with the composition according to Comparative Example 3, the V2O5 transition metal oxide content in the glass frit was less than 5 wt%, confirming problems of glass segregation and reduced density after firing.
[0076] Comparative Example 4
[0077] A glass frit with a composition of 2Na2O-14BaO-5CaO-38ZnO-20B2O3-4.5SiO2-7.5Al2O3-9V2O5 was prepared to have an average particle size of 2.0㎛. This glass frit had a glass transition temperature of 560℃ and a residual carbon content of 600ppm.
[0078] As a result of measuring the physical properties of an MLCC made with the composition according to Comparative Example 4, it was confirmed that the glass transition temperature (Tg) of the glass frit was high at 560°C and the sintering density was low because the content of BaO+CaO+B2O3 was added at less than 40 wt%.
[0079] Comparative Example 5
[0080] A glass frit with a composition of 39BaO-5CaO-22ZnO-17B2O3-3SiO2-5Al2O3-9V2O5 was prepared to have an average particle size of 3.0 μm. This glass frit had a glass transition temperature of 512°C and a residual carbon content of 980 ppm.
[0081] A photograph of an MLCC fabricated with the composition according to Comparative Example 5 is shown in Fig. 5. Although a dense external electrode layer could be formed overall, some precipitation on the glass surface was observed, and it was confirmed that a reaction layer was not formed due to the low ZnO content. Accordingly, no improvement in internal-external electrode contact and consequent improvement in ESR were observed.
[0082] Comparative Example 6
[0083] A glass frit with a composition of 43.5BaO-4CaO-19ZnO-16.5B2O3-4.5SiO2-12.5Al2O3 was prepared to have an average particle size of 3.0㎛. This glass frit had a glass transition temperature of 555℃ and a residual carbon content of 1800ppm.
[0084] The composition according to Comparative Example 6 exhibited a high glass transition temperature due to a high BaO+CaO content and a high BaO+CaO+B2O3 content of 64%. Consequently, glass fluidity decreased, leading to reduced calcination density. Furthermore, despite the absence of alkali metal oxides in the composition, the high residual carbon content resulted in multiple blisters. Additionally, the composition had a low ZnO content and transition metal oxides (Tm x O y Since ) was not added, the reaction layer could not be formed and the ESR characteristics could not be improved.
[0085] Comparative Example 7
[0086] A glass frit with a composition of 4Na2O-4BaO-4CaO-36ZnO-17B2O3-25SiO2-2.5Al2O3-7.5MnO2 was prepared to have an average particle size of 2.0㎛. This glass frit had a glass transition temperature of 555℃ and a residual carbon content of 660ppm.
[0087] As a result of measuring the physical properties of an MLCC fabricated with the composition according to Comparative Example 7, the glass transition temperature of the glass frit was found to be high due to the excessive SiO2 content in the glass frit, and although the excessive Na2O content increased reactivity with the ceramic body, it caused cracking, which actually reduced the contact between the inner and outer electrodes, and thus the ESR was not improved. ESR is reduced when the electrode contact area is maximized, but it appears that the ESR characteristics were degraded because the glass formed a thick layer between the inner and outer electrodes, which reduced the contact. This implies that in high-voltage models where high current flows, if the resistance increases due to a reduction in the conductor cross-sectional area, the ESR characteristics deteriorate.
[0088] The present invention has been described with reference to the embodiments illustrated in the drawings, but this is merely illustrative, and those skilled in the art will understand that various modifications and equivalent alternative embodiments are possible therefrom. Accordingly, the true technical scope of protection of the present invention should be determined by the technical spirit of the appended claims.
Claims
Claim 1 Conductive metal powder; and aBaO-bCaO-cZnO-dB2O3-eSiO2-fAl2O3-gTM x O y Glass frit composed of the chemical formula -hA2O; comprising, wherein TM is a transition metal selected from the group consisting of vanadium (V) and manganese (Mn), A is an alkali metal selected from the group consisting of lithium (Li), sodium (Na) and potassium (K), x,y>0, a+b+c+d+e+f+g+h=100 wt%, and 0 <a+b<45, 30<c<40, 15≤d≤25, 0<e<10, 0<f<10, 5<g<10, 0.5≤h≤2, 40≤a+b+d≤61 인,외부전극용 도전성 페이스트 조성물. Claim 2 A conductive paste composition for an external electrode according to claim 1, wherein the content of the glass frit is 5 to 20 parts by weight per 100 parts by weight of the composition. Claim 3 A conductive paste composition for an external electrode, characterized in that, in claim 1, the conductive metal powder is copper (Cu) powder. Claim 4 A conductive paste composition for an external electrode according to claim 3, wherein the copper (Cu) powder has an average particle size of 0.1 to 5 μm. Claim 5 A conductive paste composition for an external electrode according to claim 1, characterized in that the average particle size of the glass frit is 2 μm or more and 3 μm or less. Claim 6 A conductive paste composition for an external electrode, characterized in that it has a viscosity of 20 to 60 Pa·S in claim 1. Claim 7 In claim 1, the glass transition temperature (Tg) of the glass frit is 520 o C or higher 550 o A conductive paste composition for external electrodes, characterized by having a carbon content of C or less and a residual carbon content of 450 ppm or more and less than 1,000 ppm after firing. Claim 8 An external electrode obtained by firing a conductive paste composition for an external electrode described in any one of claims 1 to 7. Claim 9 A multilayer ceramic capacitor having an external electrode as described in claim 8. Claim 10 A multilayer ceramic capacitor according to claim 9, wherein the multilayer ceramic capacitor has a form in which dielectric layers and internal electrodes are alternately stacked, and the external electrode is electrically connected to the internal electrode by a reaction layer formed at least one interface between the internal electrode and the external electrode.
Citation Information
Patent Citations
Paste compound for termination electrode and multilayer ceramic electronic component by using the same and manufacturing method thereof
KR1020150049508A
Multi-layer ceramic capacitor
KR1020160042609A
Conductive paste composition for termination electrode of multilayer ceramic capacitor
KR1020220170399A
